2023
DOI: 10.1021/acs.chemrev.2c00430
|View full text |Cite
|
Sign up to set email alerts
|

Organic Peroxides in Aerosol: Key Reactive Intermediates for Multiphase Processes in the Atmosphere

Abstract: Organic peroxides (POs) are organic molecules with one or more peroxide (−O−O−) functional groups. POs are commonly regarded as chemically labile termination products from gas-phase radical chemistry and therefore serve as temporary reservoirs for oxidative radicals (HO x and RO x ) in the atmosphere. Owing to their ubiquity, active gasparticle partitioning behavior, and reactivity, POs are key reactive intermediates in atmospheric multiphase processes determining the life cycle (formation, growth, and aging),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 498 publications
0
60
1
Order By: Relevance
“…The formed geminal diols and α-HHs would be in equilibrium with their corresponding carbonyls and H 2 O/H 2 O 2 in atmospheric condensed phases. By possessing a hydroperoxide (−OOH) moiety, α-HHs may be involved in reactions with other species of atmospheric condensed phases . In contrast with previous experiments examining the photochemical oxidation of Levo, we could not find evidence for the formation of Levo+≥4O products and smaller mass carboxylic acids, implying that Fenton oxidation under the present conditions was rather mild.…”
Section: Atmospheric Implicationscontrasting
confidence: 96%
“…The formed geminal diols and α-HHs would be in equilibrium with their corresponding carbonyls and H 2 O/H 2 O 2 in atmospheric condensed phases. By possessing a hydroperoxide (−OOH) moiety, α-HHs may be involved in reactions with other species of atmospheric condensed phases . In contrast with previous experiments examining the photochemical oxidation of Levo, we could not find evidence for the formation of Levo+≥4O products and smaller mass carboxylic acids, implying that Fenton oxidation under the present conditions was rather mild.…”
Section: Atmospheric Implicationscontrasting
confidence: 96%
“…ROOHs have also been shown to hydrolyze in aqueous aerosols and form carbonyl compounds and H 2 O 2 ; 93 this is enabled by the presence of water 116 and catalyzed by acids. 96 For example, ROOHs generated from the ozonolysis of terpenes have been shown to readily decompose into aldehydes and H 2 O 2 on acidified aerosols, 96 including when acidified with small organic acids, which are ubiquitous species indoors.…”
Section: Discussionmentioning
confidence: 99%
“…In this work, 1,2-ISOPOOH was used as a model indoor ROOH to represent the dynamics of this class of indoor pollutants with real indoor surfaces. Like outdoors, 56,93,141–144 there is likely a plethora of ROOH compounds present indoors, due particularly to oxidation of indoor terpenes ( e.g. , from air fresheners, cleaning products, wood materials) 145,146 but also from polycyclic aromatic hydrocarbons ( e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, this will lead to a significant underestimation of the OP signal when using traditional offline analysis, especially if filter samples are not analyzed immediately. In a recent review Wang et al, 2023(Wang et al, 2023 reported lifetimes for peroxide from seconds to days. Therefore, the decomposition of these peroxides may contribute to reduced OP on filter samples, as they may well degrade prior to analysis.…”
Section: 5mentioning
confidence: 99%